2020
DOI: 10.1590/0102-311x00148020
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 e ambiente alimentar digital no Brasil: reflexões sobre a influência da pandemia no uso de aplicativos de delivery de comida

Abstract: COVID-19 and the digital food environment in Brazil: reflections on the pandemic's influence on the use of food delivery apps COVID-19 e ambiente alimentar digital no Brasil: reflexões sobre a influência da pandemia no uso de aplicativos de delivery de comida COVID-19 y ambiente alimentario digital en Brasil: reflexiones sobre la influencia de la pandemia en el uso de aplicaciones de entrega de comida

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 8 publications
(9 reference statements)
0
13
0
18
Order By: Relevance
“…According to Botelho et al (2020) , the context of physical distancing contributes to the adoption of food delivery, as long as food services follow hygienic-sanitary guidelines. Thus, more Brazilians are choosing to receive food at home, considering that using this technological solution is safer than going out to eat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Botelho et al (2020) , the context of physical distancing contributes to the adoption of food delivery, as long as food services follow hygienic-sanitary guidelines. Thus, more Brazilians are choosing to receive food at home, considering that using this technological solution is safer than going out to eat.…”
Section: Discussionmentioning
confidence: 99%
“…Rezende et al (2020) also indicated that large companies of the food delivery business, such as Ifood, Rappi and Uber Eats, had a bigger growth than usual. Additionally, its customers started to buy larger quantities per order, more frequently and at times different from those when consumption peaks usually occurred, including breakfast, afternoon and lunch ( Botelho et al, 2020 ). In this context, it is important to highlight the need for public health measures to discourage the consumption of ultra-processed foods, such as the adoption of packaging with frontal warning, the taxation of sugary drinks and the regulation of advertising and environments ( Swinburn et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os setores alimentícios mesmo seguindo todas as recomendações tiveram que se reinventar para manter seus estabelecimentos abertos, uma das estratégias encontradas foram os serviços delivery, sendo esse serviço um meio alternativo para que os comércios permaneçam em funcionamento (BOTELHO et al, 2020;SEBRAE, 2020).Com a reabertura gradativa dos comércios de todas as regiões, foram criados vários guias, manuais e notas técnicas principalmente pela Organização da Saúde (OMS), ANVISA e ABRASEL a fim de orientar e definir diretrizes aos colaboradores de maneira a garantir o seguro funcionamento dos estabelecimentos (FINKLER et al, 2020).…”
Section: Fonte: Brasil (2021)unclassified
“…É notável o crescimento do setor alimentício nos últimos anos, em especial, o mercado de pizzarias; movimentando cerca de 22 bilhões de reais por ano (Silva, 2019). Neste sentido, também vem crescendo cada vez mais, os serviços de delivery, que associado ao atual momento de distanciamento físico, devido ao COVID-19, tornou-se indispensável (Botelho, 2020).…”
Section: Introductionunclassified